Infant urinary bisphenol A concentrations in relation to child neurodevelopment at 2 years of age - Ying Zhao; Yanbin Ye; Huifang Lin; Xiaolin Ruan; Yong Guo; Jieling Wu (Ecotoxicology and Environmental Safety)
Prenatal and childhood bisphenol A (BPA) exposures are known to negatively affect neurodevelopment, but the impact of exposure during the infancy period remains unclear. This study aimed to investigate BPA exposure at 1 and 6 months of age and its correlation with neurodevelopmental scores at 2 years of age, focusing on age-specific effects and potential sex differences. In the cohort study conducted from May 2021 to December 2023, urine samples were collected from infants at 1 and 6 months, followed by neurodevelopmental assessments at 2 years of age. Of the 240 and 210 urine samples collected at 1 and 6 months, urinary BPA was detected via liquid chromatographytandem mass spectrometry in 93.7 and 93.8 %, with median concentrations of 2.79 and 4.04 μg/L, respectively. At the 1-month assessment, no statistically significant associations were observed between urinary BPA concentrations and any neurodevelopmental outcomes in either male or female infants (all adjusted P > 0.05). However, at the 6-month assessment, significant inverse associations were identified exclusively in female infants. Specifically, higher urinary BPA concentrations at 6 months were independently associated with lower scores in the gross motor domain (adjusted β = −3.33; 95 % CI: −6.36, −0.30; P = 0.032), adaptive behavior domain (adjusted β = −5.01; 95 % CI: −9.28, −0.74; P = 0.022), personal-social skills (adjusted β = −6.12; 95 % CI: −11.29, −0.94; P = 0.021), and the total neurodevelopmental score (adjusted β = −4.21; 95 % CI: −8.02, −0.40; P = 0.031) after controlling for relevant confounders. In contrast, no significant associations were detected between 6-month BPA concentrations and neurodevelopmental outcomes in male infants (all adjusted P > 0.05). Our study identified neurodevelopmental effects of BPA as specific to both exposure timing and infant sex, highlighted by the finding that exposure at 6 months was negatively associated with neurodevelopmental scores in females.